Development of Electro-Mechanical Impedance-Based Damage Detection Technique for Structural Health Monitoring - Hrairi, Meftah ([s.n], 2015)
Impedance-based structural health monitoring techniques have been developed as a promising tool for real-time structural damage assessment and are considered as a new non-destructive evaluation method. Active elements of the technique are Piezoelectric Wafer Active Sensor (PWAS) bonded on the structure. Modelling and simulation of PWAS and host structure play an important role in the SHM applications with PWAS. For decades, finite element method has been extensively applied in the analysis of piezoelectric materials and structures. It is gaining popularity due to its potential of reducing maintenance costs while increasing safety and reliability. This thesis presents the results of finite element analyses performed for a freely suspended piezoelectric (PZT) patches as well as a cantilever aluminium beam which has been made by 1100 alloy with bonded piezoelectric transducer. Modelled structure was excited to vibrate at high frequency range and electromechanical impedance (EMI) plots were obtained from the harmonic analysis. The EMI signature of the beam was found for different position of the PWAS patch. The study shows that sensor position may directly control the EMI signature. Notches and loads were introduced in the beam and the damage metrics were used to assess qualitative changes in structural properties of the system. Furthermore, a parametric study of the effects of different variables such as patch type and size, notch shape and size, glue thickness, patch position were carried out. The numerical results were confirmed either experimentally using laboratory equipment or with results available in the open literature and a good agreement was observed. The results showed that this method is accurate to monitor the structure’s health. It was found that EMI method was able to detect the presence of very small damages. Hence, this system can be used for continuous monitoring of the structures.